Intermetallic phase kinetic formation and thermal crack development in galvanized DCI (Fracture and Structural Integrity, 2019)
A new class of material characterized by mechanical properties close to the traditional low and medium carbon steel is the Ductile Cast Irons (DCIs). High castability and low production costs allow them to be used in many fields, ranging from automotive to piping. In this class of iron-based alloy the content of carbon is mainly localized in the graphite nodules, which are dispersed in a metallic matrix characterized by different phases: ferrite, austenite, pearlite, martensite or their mix, depending on the chemical composition and the heat treatment. Metallic matrix is subjected to the corrosion phenomenon, and, for this reason, the study and the development of traditional and innovative protection techniques are important, mainly in critical applications. Hot dip galvanizing is one of the investigated protections because the zinc is able to protect the iron-based alloys thanks to the reduction potential that is lower than the iron one.In this work, a ferritic-pearlitic DCI (GS500) is galvanized by using a pure Zn bath at 440°C in order to generate a zinc coating at different dipping time. The presence of thermal cracks is observed by means of a Scanning Electron Microscope (SEM).
Keywords: Hot Dip Galvanizing; Ductile Cast Iron; Damage; Stress field